Constitutive Penicillinase Formation in Staphylococcus aureus Owing to a Mutation Unlinked to the Penicillinase Plasmid - Cohen, Sidney (1968)
Previously described penicillinase-constitutive mutations in Staphylococcus aureus are caused by genetic lesions in a regulator gene (or genes) on the penicillinase plasmid in close linkage to the structural gene. This report describes a new class (R2(−)) of penicillinase-constitutive mutants of S. aureus unlinked to the plasmid. By transductional analysis, the penicillinase plasmids in these mutants were wild type. Wild-type plasmids transduced into penicillinase-negative (plasmid loss) derivatives of R2(−) mutants produced penicillinase constitutively in amounts comparable to a fully induced culture of the wild-type strain. Penicillinase production in R2(−) mutants was maximal at 30 to 32 C and was much reduced at 40 C.